1998
DOI: 10.1007/s00585-998-0148-0
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous measurements of X-rays and electrons during a pulsating aurora

Abstract: Abstract. The PULSAUR II rocket was launched from Andøya Rocket Range at 23.43 UT on 9 February 1994 into a pulsating aurora. In this paper we focus on the observations of precipitating electrons and auroral X-rays. By using models it is possible to deduce the electron energy spectrum from X-ray measurements. Comparisons are made between the deduced electron fluxes and the directly measured electron fluxes on the rocket. We found the shape of the observed and the deduced electron spectra to fit very well, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…where {Pol and {P02 are the X-ray flux at zero energy and E m and Eo2 are the two characteristic energies, very often can be used to represent the X-ray flux energy spectra, {P(E) [e.g., Goldberg et al, 1982]. From a rocket experiment in the postmidnight sector during the recovery phase of a substorm [Ostgaard et al, 1998] when both X-ray measurements and electron measurements were available it was found that both the electron spectrum and the Xray spectrum could be represented by a sum of two exponentials, giving very good correlation when comparing measured and calculated electron spectra and measured and calculated X-ray spectra. To examine how good this functional fit works for the actual electron measurements, we show four spectra measured by NOAA 12 from a pass in the morning sector ( Figure 2) and four spectra measured by DMSP F13 from a pass in the midnight sector ( Figure 3).…”
Section: Electron Measurements and Functional Fitsmentioning
confidence: 99%
“…where {Pol and {P02 are the X-ray flux at zero energy and E m and Eo2 are the two characteristic energies, very often can be used to represent the X-ray flux energy spectra, {P(E) [e.g., Goldberg et al, 1982]. From a rocket experiment in the postmidnight sector during the recovery phase of a substorm [Ostgaard et al, 1998] when both X-ray measurements and electron measurements were available it was found that both the electron spectrum and the Xray spectrum could be represented by a sum of two exponentials, giving very good correlation when comparing measured and calculated electron spectra and measured and calculated X-ray spectra. To examine how good this functional fit works for the actual electron measurements, we show four spectra measured by NOAA 12 from a pass in the morning sector ( Figure 2) and four spectra measured by DMSP F13 from a pass in the midnight sector ( Figure 3).…”
Section: Electron Measurements and Functional Fitsmentioning
confidence: 99%
“…In the nightside auroral zone, pulsating aurora are prevalent after a magnetospheric substorm has occurred (Cresswell, 1972;Oguti, 1976;Nemzek et al, 1995;Jones et al, 2011). The kinetic energies of the precipitating electrons giving rise to the atmospheric optical emission are typically in the keV range (McEwan et al, 1981;Sato et al, 2004;Miyoshi et al, 2015;Tesema et al, 2020a) but also extend up into the 100s of keV range (Ostgaard et al, 1998;Miyoshi et al, 2015;Turunen et al, 2016) and down into the sub-keV range (Liang et al, 2016). Pulsating aurora are also associated with relativistic-electron microbursts of precipitation (Miyoshi et al, 2020;Kawamura et al, 2021).…”
mentioning
confidence: 99%